Holographic corrections to the Veneziano amplitude - Adi Armoni (Physics Letters B, 2017)
We propose a holographic computation of the 2→2 meson scattering in a curved string background, dual to a QCD-like theory. We recover the Veneziano amplitude and compute a perturbative correction due to the background curvature. The result implies a small deviation from a linear trajectory, which is a requirement of the UV regime of QCD.